Махновщина: деякі питання методології соціологічного аналізу. (Zaporizhzhia Historical Review, 2021)
The article examines methodological potential of N.Luhman’s system theory for the sociological analysis of N. Makhno’s insurgent movement in 1917–1920. The author comes to the conclusion, that the Ukrainian peasantry was inclined to support anarchists, but not bolsheviks. However traditional rural communities were not ready to anarchist modernization of a society.